Fusobacterium nucleatum drives CD40-mediated dendritic cell activation and Th17/Treg imbalance to exacerbate intestinal inflammation in Crohn’s disease - Wang, Mingyuan; Sun, Junjian; Yu, Jiang; Wang, Jiayun; Xu, Chenjing; Ma, Jingjing; Zhang, Hongjie (Frontiers in Immunology, 2026)
BackgroundCrohn’s disease (CD) is a chronic relapsing inflammatory bowel disease characterized by persistent mucosal inflammation and immune dysregulation. While alterations in gut microbial composition are known to contribute to CD pathogenesis, the precise mechanisms linking specific microbial species to immune dysfunction remain unclear. Here, we identify Fusobacterium nucleatum (Fn), a pathobiont enriched in CD patients, as a key driver of dendritic cell (DC) activation and downstream Th17/Treg imbalance.MethodsFecal and colonic mucosal samples from CD patients and healthy controls were analyzed by 16S rRNA sequencing. A TNBS-induced colitis model with adoptive DC transfer, was used to evaluate the impact of Fn on intestinal inflammation, DC activation and Th17/Treg balance. RNA sequencing of Fn-exposed bone marrow-derived DCs (BMDCs) identified key immune mediators. CD40 signaling was verified through inhibition with TRAF-STOP, both in vivo and in vitro.ResultsFn was significantly enriched in CD and positively associated with severity of inflammation. In mice, Fn aggravated colitis, resulting in heightened immune dysregulation, especially DC activation. Adoptive transfer of Fn-primed DCs aggravated TNBS-induced inflammation in recipient mice, accompanied by Th17/Treg imbalance. Transcriptomic analysis identified robust CD40 upregulation in Fn-exposed DCs, which was corroborated in inflamed colons from CD patients. CD40 blockade with TRAF-STOP suppressed DC activation, restored Th17/Treg balance, and ameliorated intestinal inflammation.ConclusionsThis study demonstrates that Fn exacerbates intestinal inflammation under inflammatory conditions in CD through CD40-mediated DC activation and subsequent Th17/Treg imbalance. These findings establish a novel mechanistic link between microbial dysbiosis and immune dysregulation, identifying CD40 as a promising target for microbiota-directed immunotherapy.